2019
DOI: 10.1515/cdbme-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Computer model of oxygenation in neonates

Abstract: Maintaining a prescribed peripheral oxygen saturation (SpO2) target during routine care of neonates is challenging and inspired fraction of oxygen (FiO2) titration practices differ among caregivers and centers. Algorithms for automatic feedback control of SpO2 are being developed and tested, that would adapt to the changing neonatal organism and better maintain the required SpO2 target range. While clinical data is necessary to validate differences in the titration strategies, a continuous physiological model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…We repeatedly run a 310s-long simulation that included a single desaturation episode due to apnoea. The desaturation episode was modelled based on the real clinical data of a premature male infant, 27 days old, weighing 1,019 grams that were used in our previous study [7] to preliminary validate the model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We repeatedly run a 310s-long simulation that included a single desaturation episode due to apnoea. The desaturation episode was modelled based on the real clinical data of a premature male infant, 27 days old, weighing 1,019 grams that were used in our previous study [7] to preliminary validate the model.…”
Section: Methodsmentioning
confidence: 99%
“…In different models, Sands et al showed possibilities how to describe impaired gas transfer across the alveolar-capillary membrane by ventilation-perfusion mismatch [5] or elevated alveolarcapillary diffusion resistance [6]. In our project [7], Morozoff's model was enhanced in several ways; primarily a diffusion resistance (Rdiff) has been introduced into the model and the range of some physiological parameters of the model was estimated from neonatal literature rather than scaling from adults. The search for optimal values of internal parameters of the model with respect to available neonatal clinical data raised a question of the relative influence of the parameters on the model output signal, SpO2.…”
Section: Introductionmentioning
confidence: 99%
“…In the last ten years, many articles have introduced closed-loop control algorithms of oxygenation in neonates, but a complex clinical study to compare the effectiveness of those various algorithms is still missing [6]. Clinical tests of the new oxygenation control algorithms of neonates bring safety and ethical risks, but a mathematical model of oxygenation in neonates can allow for the in silico simulation of oxygenation and preliminary comparison of the control algorithms [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%